PEMBELAJARAN SEJARAH DALAM PERSPEKTIF PEDAGOGI KRITIS - Piki Setri Pernantah (Jurnal Pendidikan, 2020)
This article is a theoretical study using the method of literacy study. It aims to discuss and study historical learning in a new perspective. Learning of history should be oriented to provide historical knowledge and introduce the noble values of the nation. Because, those two things will not have meaning for the lives of students if they do not understand the meaning of every historical event that they have learned. Efforts to realize meaningful historical learning, related to students' actions for reflective thinking. One thing that cannot be separated from the study of critical pedagogy is reflective thinking. Applying critical pedagogy in learning history, which means emphasizing critical theory as an analytical tool for reading various historical realities in learning. It is expected that students will be able to interact with each other and study various historical realities so that they can reflect on themselves and think critically about these realities. Discussing the learning of history in the concept of critical pedagogy is a new approach that seeks to help students in the process of historical learning. So that they can question and criticize every material in historical learning so that it gives birth to critical-reflective thinking that makes students able to learn and interpret every historical fact and historical learning material in school.